(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
This article examines the development of the speech of students-philologists when teaching the Russian language, which at present the speech of students leaves much to be desired. Today, more than ever, it is especially important for a teacher to awaken interest in the sounding word, to teach children to feel its true taste and purpose. Undoubtedly, this process is long and painstaking, requiring a certain organization, system, methodological ingenuity and invention, practical experience. At the lessons of the Russian language and not only, children need to be taught to use the Russian word, to understand and feel it, to strive to develop their speech, to improve their speech creativity